The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/age.12409
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association reveals the locus responsible for four‐horned ruminant

Abstract: SummaryPhenotypic variability in horn characteristics, such as their size, number and shape, offers the opportunity to elucidate the molecular basis of horn development. The objective of this study was to map the genetic determinant controlling the production of four horns in two breeds, Jacob sheep and Navajo-Churro, and examine whether an eyelid abnormality occurring in the same populations is related. Genome-wide association mapping was performed using 125 animals from the two breeds that contain two-and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 17 publications
4
32
0
1
Order By: Relevance
“…Dense genotyping also provides a means of mapping desired traits to specific regions of the genome designated quantitative trait loci (QTL)[22]. This identifies not only phenotypes controlled by single genes, but complex traits produced by the interaction of many genes[1, 4, 23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…Dense genotyping also provides a means of mapping desired traits to specific regions of the genome designated quantitative trait loci (QTL)[22]. This identifies not only phenotypes controlled by single genes, but complex traits produced by the interaction of many genes[1, 4, 23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been found that HOXD11 mutant mice exhibit supernumerary lumbar vertebrae, indicating that HOXD gene expression anomalies can affect vertebral column development (Davis and Capecchi, 1994). Interestingly, an association has been found between four-horned and polled phenotypes and the presence of "split-eyelid abnormalities", which also sporadically occur in Jacob sheep (Kijas et al, 2016). This indicates that deviations from the "normal" two-horned state may be linked to abnormalities in various anatomical regions.…”
Section: Histopathologic Examinationmentioning
confidence: 98%
“…In addition, mild condylar asymmetry was observed in six out of eight clinically-unaffected polycerate Jacob skulls (Ellis and Brown, 2014). This suggests that while there appears to be an association with the polycerate gene, which is dominant over the two-horned phenotype (Kijas et al, 2016), the penetrance is variable. In the present case the sire consistently produced clinically-normal lambs for four years, and while the home-bred dam was primiparous, she and the affected lamb's twin sibling were healthy.…”
Section: Histopathologic Examinationmentioning
confidence: 99%
See 2 more Smart Citations